Highly porous melamine-formaldehyde monoliths with controlled hierarchical porosity toward application as a metal scavenger. Issue 8 (19th March 2021) - Nakanishi, Yuki; Hara, Yosuke; Miyamoto, Riichi; Nakanishi, Kazuki; Kanamori, Kazuyoshi
Abstract : Hierarchically porous melamine-formaldehyde monoliths were prepared via sol–gel accompanied by phase separation, followed by a hydrothermal process. The obtained monoliths showed efficient adsorption of precious metal ions. Abstract : We report a new synthetic strategy for melamine-formaldehyde (MF) monoliths with controlled hierarchical porosity toward metal-ion scavengers. The obtained MF monoliths possessed micro-, meso- and macroporosity, which allowed efficient adsorption performance of precious metal ions in water. Applications such as recovery/removal of metal ions are expected.